Trump-Kim Summit 2018 : Russia’s Cautious Response - Cheang, Chris (2018)
Russia’s relatively cautious reaction to the Singapore Summit’s outcome suggests that it seeks a role in the denuclearisation efforts of the Korean Peninsula.